Attachment Theory as a Framework for Understanding Responses to Social Exclusion. Issue 7 (8th July 2013) - Maxwell, Jessica A.; Spielmann, Stephanie S.; Joel, Samantha; MacDonald, Geoff
Abstract We argue that attachment theory may provide a useful framework for understanding individuals' reactions to social exclusion. Attachment theory suggests that social exclusion should prompt an individual to seek comfort from an accepting attachment figure. However, most experimental studies constrain individuals from seeking out an attachment figure to quell their distress, and may interfere with the process of recruiting internalized attachment figures. When the goal of recruiting attachment figure support is blocked, individuals may adopt deactivating strategies, such as emotional numbing, to reduce their distress. Alternatively, individuals may adopt hyperactivating strategies, such as ingratiating behaviors, to seek proximity to attachment figure substitutes. We conclude with recommendations for future avenues of exclusion research stemming from attachment theory.